2023
DOI: 10.3390/biomedicines11041114
|View full text |Cite
|
Sign up to set email alerts
|

Cubosomes in Drug Delivery—A Comprehensive Review on Its Structural Components, Preparation Techniques and Therapeutic Applications

Abstract: Cubosomes are lipid vesicles that are comparable to vesicular systems like liposomes. Cubosomes are created with certain amphiphilic lipids in the presence of a suitable stabiliser. Since its discovery and designation, self-assembled cubosomes as active drug delivery vehicles have drawn much attention and interest. Oral, ocular, transdermal, and chemotherapeutic are just a few of the drug delivery methods in which they are used. Cubosomes show tremendous potential in drug nanoformulations for cancer therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 100 publications
0
13
0
Order By: Relevance
“…These cubosomes are considered to be more stable than liposomes for having liquid crystalline membrane design along with a stronger potential to surround and encapsulate hydrophobic chemotherapeutic drugs which may provide continuous release of drugs over long periods . The major benefit of this cubosome over any other nanoparticle including liposome that it may allow more hydrophobic drugs with a larger hydrophobic area still allowing for hydrophilic drug loading . Cubosomes are regarded as potential carriers for various routes of administration because of unique properties such as thermostability, adhesion, the ability to encapsulate drugs, and the capacity to sustain release .…”
Section: Advantages Of Cubosomes Over Other Nanocarriersmentioning
confidence: 99%
“…These cubosomes are considered to be more stable than liposomes for having liquid crystalline membrane design along with a stronger potential to surround and encapsulate hydrophobic chemotherapeutic drugs which may provide continuous release of drugs over long periods . The major benefit of this cubosome over any other nanoparticle including liposome that it may allow more hydrophobic drugs with a larger hydrophobic area still allowing for hydrophilic drug loading . Cubosomes are regarded as potential carriers for various routes of administration because of unique properties such as thermostability, adhesion, the ability to encapsulate drugs, and the capacity to sustain release .…”
Section: Advantages Of Cubosomes Over Other Nanocarriersmentioning
confidence: 99%
“…[27][28][29][30] Monoolein (MO), an uncharged single-chain amphiphile with an ester linkage, was used as a nontoxic monoacylglycerol that forms nonlamellar lipid cubic phases. [31][32][33][34] For comparison, DMPC was employed as a lamellar type of phospholipid forming vesicle drug delivery nanocarriers (detailed in Table S1). The nanocarriers loaded with GB or coloaded with GB and quercetin were stabilized by the surfactant agents Pluronic F127 or DOPE-PEG 2000 (Table S1).…”
Section: Lipid Nanoparticles Loaded With Ginkgolide B and Quercetinmentioning
confidence: 99%
“…Among them, cubosomes and liposomes offer many advantages, such as enhanced bioavailability, cellular uptake, good biocompatibility and biodegradability, ease of surface functionalization with targeting ligands, and enhanced solubility of poorly soluble drugs. , Cubosomes are a class of lipid nanoparticles formed from the inverse bicontinuous cubic phases (Q 2 ) of the parent lipid dispersed in aqueous solution into nanoparticulate forms in the presence of steric stabilizers. ,, The Q 2 phase consists of a continuous lipid bilayer depicted by a periodic minimal surface and two nonintersecting water channels. Due to the amphiphilic nature of the Q 2 phase, cubosomes can encapsulate hydrophilic, hydrophobic, and amphiphilic drugs. , In comparison to liposomes, cubosomes offer larger internal surface areas and unique fusogenic membrane curvature due to their periodic porous cubic structure, enabling higher drug loading capacity and encapsulation efficiency (EE) for various substances such as anti-cancer drugs, siRNA, peptides, and proteins, as well as improved intracellular uptake and endosomal escape. , These unique attributes position them as ideal bioactive agent carriers to penetrate many biological barriers including the BBB. , Several studies have shown that cubosomes can efficiently deliver drugs across the BBB. Mohammad et al utilized cubosomes to encapsulate phenytoin, an antiseizure medication, showing enhanced phenytoin brain accumulation in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid nanoparticles have been extensively researched for various applications, such as in vitro and in vivo BBB penetration for brain cancer treatment, whereas ligandconjugated cubosomes and their ability to cross BBB remain scarcely studied. 11,24,27,[29][30][31][32]37,38,41 In this study, we aimed to develop Ang2-conjugated cubosomes for the first time to increase BBB penetration as well as glioblastoma cell uptake toward a more efficient treatment of brain cancer. In our previous studies, we successfully synthesized a series of 46,47 In this study, we selected the polymer PEG 114b-PDMAEMA 17 -b-PTBA 9 -RAFT (Figure 1) to formulate Ang2-conjugated MO-based cubosomes loaded with cisplatin (CDDP) and temozolomide (TMZ) as anticancer, poorly soluble model drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation